2010
DOI: 10.1124/jpet.110.173708
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Glutathione in Ameliorating Sulfur Mustard Analog-Induced Toxicity in Cultured Skin Epidermal Cells and in SKH-1 Mouse Skin In Vivo

Abstract: Exposure to chemical warfare agent sulfur mustard (HD) is reported to cause GSH depletion, which plays an important role in HD-linked oxidative stress and skin injury. Using the HD analog 2-chloroethyl ethyl sulfide (CEES), we evaluated the role of GSH and its efficacy in ameliorating CEES-caused skin injury. Using mouse JB6 and human HaCaT epidermal keratinocytes, we observed both protective and therapeutic effects of exogenous GSH (1 or 10 mM) in attenuating a CEES-caused decrease in cell viability and DNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 33 publications
3
56
0
1
Order By: Relevance
“…Although AEOL 10150 did not appear to improve GSH levels, this effect may be complicated by the formation of SM-GSH adducts which would not have been detected by the HPLC methods used here (Batal et al, 2015;Mol et al, 2008). Other publications investigating oxidative stress and vesicants have concluded that reductions in the measured markers of oxidative stress are linked to lowered toxicity (Gould et al, 2009;Laskin et al, 2010;O'Neill et al, 2010;Tewari-Singh et al, 2011;Ucar et al, 2007). Our results support the hypothesis that AEOL 10150 lowered oxidative stress in this model, which correlated with attenuating SM toxicity.…”
Section: Discussionsupporting
confidence: 80%
“…Although AEOL 10150 did not appear to improve GSH levels, this effect may be complicated by the formation of SM-GSH adducts which would not have been detected by the HPLC methods used here (Batal et al, 2015;Mol et al, 2008). Other publications investigating oxidative stress and vesicants have concluded that reductions in the measured markers of oxidative stress are linked to lowered toxicity (Gould et al, 2009;Laskin et al, 2010;O'Neill et al, 2010;Tewari-Singh et al, 2011;Ucar et al, 2007). Our results support the hypothesis that AEOL 10150 lowered oxidative stress in this model, which correlated with attenuating SM toxicity.…”
Section: Discussionsupporting
confidence: 80%
“…Thiol compounds such as GSH and NAC have been suggested as potential antidotes against SM toxicity in vivo and in vitro (Amir et al, 1998;Laskin et al, 2010;Lindsay et al, 1997;Paromov et al, 2007;Tewari-Singh et al, 2011). Recent data from animal studies in a domestic swine model suggest a beneficial effect of NAC treatment, even when administered after SM exposure (Jugg et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…The presented study focussed on dose-effect relationships with particular interest on cytotoxicity and the release of pro-inflammatory cytokines. Doses of NAC (1, 5 and 10 mM) were established from the available literature on the clinical use of NAC in patients with paracetamol poisoning (Borgstrom et al, 1986;Holdiness, 1991;Shen et al, 2011) and from in vitro studies on the use of NAC against SM toxicity (Atkins et al, 2000;Tewari-Singh et al, 2011). GSH was used at identical molar concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Other mechanisms include release of reactive oxygen species, depletion of glutathione, generation of reactive nitrogen species by iNOS, and production of proinflammatory cytokines like tumor necrosis factor α. [84][85][86][87] HD is radiomimetic, meaning that it predominantly affects rapidly dividing cells in the GI tract and marrow. Basal keratinocytes are particularly vulnerable to HD, which is why skin injuries feature dermal-epidermal separation (similar histologically to toxic epidermal necrolysis syndrome).…”
Section: Pathophysiology and Clinical Carementioning
confidence: 99%